C-reactive protein trajectory to predict colorectal anastomotic leak: PREDICT Study. Issue 13 (16th July 2020) - Stephensen, B D; Reid, F; Shaikh, S; Carroll, R; Smith, S R; Pockney, P
Abstract: Background: Anastomotic leak is a common complication after colorectal surgery, associated with increased morbidity and mortality, and poorer long-term survival after oncological resections. Early diagnosis improves short-term outcomes, and may translate into reduced cancer recurrence. Multiple studies have attempted to identify biomarkers to enable earlier diagnosis of anastomotic leak. One study demonstrated that the trajectory of C-reactive protein (CRP) levels was highly predictive of anastomotic leak requiring intervention, with an area under the curve of 0·961. The aim of the present study was to validate this finding externally. Methods: This was a prospective international multicentre observational study of adults undergoing elective colorectal resection with an anastomosis. CRP levels were measured before operation and for 5 days afterwards, or until day of discharge if earlier than this. The primary outcome was anastomotic leak requiring operative or radiological intervention. Results: Between March 2017 and July 2018, 933 patients were recruited from 20 hospitals across Australia, New Zealand, England and Scotland. Some 833 patients had complete CRP data and were included in the primary analysis, of whom 41 (4·9 per cent) developed an anastomotic leak. A change in CRP level exceeding 50 mg/l between any two postoperative days had a sensitivity of 0·85 for detecting a leak, and a high negative predictive value of 0·99 for ruling it out. A change in CRP concentration of more than 50 mg/l between either days 3 and 4 or days 4 and 5 after surgery had a high specificity of 0·96–0·97, with positive likelihood ratios of 4·99–6·44 for a leak requiring intervention. Conclusion: This study confirmed the value of CRP trajectory in accurately ruling out an anastomotic leak after colorectal resection. Graphical Abstract: C-reactive protein (CRP) trajectory is accurate for ruling out anastomotic leak after colorectal surgery, and can provide reassurance for early discharge. Biomarkers help